2009
DOI: 10.1111/j.1470-6431.2009.00794.x
|View full text |Cite
|
Sign up to set email alerts
|

Do men and women really shop differently? An exploration of gender differences in mall shopping in India

Abstract: ‘Men Buy and Women Shop’ proclaims a new Wharton Research on shopping habits of the American consumer (2007). There is found to be considerable difference in the way men and women shop in the West. Is this true across cultures? Indian retailing is generating considerable interest within the country and abroad. India has been rated as the fifth most attractive emerging retail market and was ranked first in a Global Retail Development Index of 30 developing countries drawn up by A T Kearney. Organized retail, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 36 publications
2
38
1
Order By: Relevance
“…This interesting dichotomy suggests that Indian consumers are drawn to malls for the experience, but mall patronage intention is dependent upon utilitarian amenities. The results of this study contradict Kuruvilla, Joshi, and Shah's (2009) study that reported neither males nor females were utilitarian in their approach to mall shopping. Thus, it can be inferred that to attract consumers to a mall, retailers and mall management need to ensure that the mall provides consumers with experiential experiences, such as a food court and gaming arcade.…”
Section: Resultscontrasting
confidence: 83%
“…This interesting dichotomy suggests that Indian consumers are drawn to malls for the experience, but mall patronage intention is dependent upon utilitarian amenities. The results of this study contradict Kuruvilla, Joshi, and Shah's (2009) study that reported neither males nor females were utilitarian in their approach to mall shopping. Thus, it can be inferred that to attract consumers to a mall, retailers and mall management need to ensure that the mall provides consumers with experiential experiences, such as a food court and gaming arcade.…”
Section: Resultscontrasting
confidence: 83%
“…Priori segmentation approach employs consumer externalities such as age, sex among others to explain differences in consumer segments" behaviour. Following this school of thought, a number of studies have been conducted wherein gender (Michon et al 2008;Kuruvilla et al 2009), age (Anselmsson, 2006), or mother and daughter (Martin, 2009) were used to segment and explain consumer segments. Marketing academics have fiercely challenged priori methods because of its focus on external characteristics of consumers and a number of studies have suggested including other variables in explaining the differences between segments" behaviour (Gonzalez-Hernandez and Orozco-Gomez, 2012).Also, Harrison (1995) posits that consumer buying behaviour is not primarily dependent on those external characteristics.…”
Section: Review Of Related Literature: Prior Research On Predictors Tmentioning
confidence: 99%
“…Women associate buying with leisure, shopping plays an emotional, psychological and symbolic role. Furthermore, women spend twice as long time in a shop as men and the typical window-shopper is a woman (Kuruvilla et al, 2009). Rocha (2005) study found that women are more fashion concerned; they give more attention to their bodies and give higher consideration to clothes to express themselves with extremely higher level than men.…”
Section: Women Attitude Towards Fashion Clothingmentioning
confidence: 99%